L’expression émotionnelle verbale et para-verbale de l’image linguistique du Juif dans le cyberespace français et polonais sur l’exemple de l’affaire DSK - Pirogowska, Ewa (Studia Romanica Posnaniensia, 2015)
The present paper comes in the wake of ‘Discours 2000’ conference. It aims at the synthesis of anti-Semitic verbal acts showing an entrenchment in linguistic stereotypes picked put in Polish and French web forums. A bundle of anti-Semitic interpretations have been selected from discussions dealing with acclaimed cases of Dominique Strauss-Kahn. It is demonstrated how a given speech act can be knowingly complemented with extra-verbal elements so that its interpretation becomes unambiguous. The examples brought under discussion show to what extent the linguistic concept of Jews is ingrained in today’s culture.